E-Library for Blankspot Areas at SMP Negeri Satap 1 Kolaka Utara - Sumihar, Yoel Pieter; Adinda, Adinda; Bantun, Suharsono; Jum'ah, Muhammad Na'im Al Jum'ah (Digital Innovation, 2024)
Digital libraries (digital libraries) or also known as electronic libraries (e-libraries) are introduced with the advantage of providing collections in electronic form that can be accessed by users without limitations of place and time by using electronic media such as computers, laptops or gadgets connected to computers. The E-Library information system for areas without a signal at SMPN Satap 1 Kolaka Utara is a data processing system that is enabled to process new member registration data, visit data processing, transaction data processing, book data processing, and fine processing. The research method uses the method of literature study, observation, interviews, and the system development method uses the waterfall. The analysis and design tools used are data flow diagrams (DFD) and database design using Entity Relationship Diagrams (ERD), the programming language used is hypertext preprocessor (PHP), and the database uses MySQL. The test method uses Blackbox and UAT testing. From the results of the discussion in the previous chapters, it can be concluded that the E-Library information system for areas without a signal at SMPN Satap 1 Kolaka makes it easy for members to read books offline and makes it easier to manage book data and borrow books.